Contribuição para o conhecimento da Mimosicerya hempeli (Cockerell, 1899) (Homoptera. Margarodidae) e de seu predador Exoplectra erythrogasfer Mulsant, 1851 (Coleoptera, Coccinellidae) - Mariconi, Francisco A. M.; Zamith, Adiei P. L. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
This paper deals with Mimosicerya hempeli (Cock., 1899) (Homoptera, Margarodidae) and its predator, the ladybeetle Exo-plectra erythrogaster Muls., 1851 (Coleoptews, Coccinellidae), which were found to occur at Piracicaba, State of São Paulo, Brasil. The first is a pest of "cássia imperial" (Cassia fistula L.), and several other trees. As those insects are little known, a few bionomical notes and descriptions of some of their stages are presented. The adult scales proved to be very resistant to an application of mineral oil plus malathion. Methyl Demeton applied with irrigation water showed no control. The same insecticide injected into the trunk gave very poor results.